1990
DOI: 10.3109/08923979009006468
|View full text |Cite
|
Sign up to set email alerts
|

Histamine Blocks Interleukin 2 (IL-2) Gene Expression and Regulates IL-2 Receptor Expression

Abstract: Histamine inhibited the proliferative response of human peripheral blood mononuclear cells (PBMC) to the T cell mitogen Phytohemagglutinin-P (PHA-P) in a dose-dependent fashion. This inhibition was mediated via the H2 receptor since cimetidine, a known H2 antagonist, removed the inhibition, whereas the addition of the H1 antagonist Diphenhydramine did not. Inhibition occurred during the inductive phase of the cell cycle, since histamine added 24 hours after PHA-P stimulation had no effect on subsequent T cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…These data suggest that modulation of lymphocyte functions may occur via engagement of the H 1 R under physiological conditions. In contrast, several investigators reported in vitro modulation of lymphocyte functions, like inhibition of mitogen-induced proliferation [31][32][33] or cytokine production [34,35] following activation of the H 2 R.…”
Section: Histamine Plasma Concentrations and Lymphocyte Hr Dissociatimentioning
confidence: 99%
See 1 more Smart Citation
“…These data suggest that modulation of lymphocyte functions may occur via engagement of the H 1 R under physiological conditions. In contrast, several investigators reported in vitro modulation of lymphocyte functions, like inhibition of mitogen-induced proliferation [31][32][33] or cytokine production [34,35] following activation of the H 2 R.…”
Section: Histamine Plasma Concentrations and Lymphocyte Hr Dissociatimentioning
confidence: 99%
“…Histamine inhibited mRNA expression and secretion of IL-2 at an early phase of T cell activation. Furthermore, no inhibition of IL-2 receptor expression could be found, and exogenous IL-2 reversed the antiproliferative effect of histamine [34].…”
Section: Inhibition Of Mitogen-induced Proliferation and Alloreactivementioning
confidence: 99%
“…On the other hand, histamine inhibited the phytohemagglutinin stimulation of human peripheral T-cells in the early phase by decreasing the expression of IL-2, acting via H2 receptors. The expression of IL-2 receptors was unchanged or even elevated, and exogenous IL-2 could prevent this inhibitory effect demonstrating that IL-2 sensitivity was unaltered [14]. In various subsets of CD4 + human T-cells histamine reduces the production of IL-2 and IFN-g [15], but there are also data about IFN-ginducing effects of histamine as well (in human T-cell clones isolated from airways (bronchoalveolar lavage fluid (BAL)) and blood) [16].…”
Section: Histamine and The Regulation Of Th1-th2 Balancementioning
confidence: 99%
“…Cimetidine (CIM) and other antagonists have been used for many years to control gastric acid secretion in humans and in domestic species. It has been shown that at least two of the compounds in this class, CIM and ranitidine, bind to the heme‐iron portion of CYP (Rendic? et al ., 1984) to inhibit CYP activity, producing a decrease in the biotransformation of various xenobiotics which are metabolized by the CYP monooxygenases (Rendic?…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that at least two of the compounds in this class, CIM and ranitidine, bind to the heme‐iron portion of CYP (Rendic? et al ., 1984) to inhibit CYP activity, producing a decrease in the biotransformation of various xenobiotics which are metabolized by the CYP monooxygenases (Rendic? et al ., 1984; Ioannoni et al ., 1986).…”
Section: Introductionmentioning
confidence: 99%